2011
DOI: 10.1002/cjce.20578
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mechanism of low‐density particle and liquid mixing process in a stirred vessel

Abstract: In order to investigate the mechanism of the low‐density solid particle and liquid mixing process, a specialised agitator structure was used. Both computational fluid dynamics simulation and experiments were carried out to study the two‐phase mixing characteristics in the stirred vessel. The mixing process was captured by snapshots. The flow field and solid phase volume fraction evolution were analysed. Experimental and numerical results agreed well with each other. Solid particles floating on the liquid surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The drawdown of floating particles in stirred tanks was recently investigated by using the E-L approach (Waghmare et al, 2011) as well as the E-E approach (Chen et al, 2012). Kresta (2008, 2009) …”
Section: Particle Shape and Typementioning
confidence: 99%
“…The drawdown of floating particles in stirred tanks was recently investigated by using the E-L approach (Waghmare et al, 2011) as well as the E-E approach (Chen et al, 2012). Kresta (2008, 2009) …”
Section: Particle Shape and Typementioning
confidence: 99%
“…Moreover, the accuracy of CFD predictions has been validated, especially in terms of σ or other mixing parameters, in sinking solid‐liquid systems . CFD studies on N CS for floating solids, however, can be hardly found in the open literature …”
Section: Introductionmentioning
confidence: 99%